SAT0369 Weight Gain in Anca-Associated Vasculitis Is Independent of Glucocorticoid Dosing. (15th July 2016) - Wallace, Z.; Miloslavsky, E.; Unizony, S.; Lu, L.; Specks, U.; Hoffman, G.; Kallenberg, C.; Langford, C.; Merkel, P.; Monach, P.; Seo, P.; Spiera, R.; et al.
Abstract : Background: The treatment of ANCA-associated vasculitis (AAV) includes high doses of glucocorticoids, the use of which has been associated with increased body-mass index (BMI) 1 . A previous study suggested that this change in BMI is independent of glucocorticoid exposure 2 . Objectives: We sought to evaluate whether increases in BMI are related more directly to improved disease control than to glucocorticoid use. Methods: We analyzed AAV patients enrolled in the Rituximab in ANCA-Associated Vasculitis (RAVE) trial 3 . Details regarding glucocorticoid exposure before and during the trial were collected, as were regular measurements of BMI and disease activity. We used multivariate linear regression to adjust for important confounders of the relationship between glucocorticoid exposure and BMI changes. We used analysis of response profile to evaluate differences in BMI over time between subgroups and mixed effects models to determine the relationship between disease activity and change in BMI. Results: Of the 197 patients enrolled in RAVE, 99 (50%) were male and the mean age was 52.8 (±15.5) years. The baseline BVAS/WG was 8.0 (±3.1). The majority (75%) had granulomatosis with polyangiitis, and PR3-ANCA+ was the most common (67%) ANCA specificity. The baseline BMI was 28.8 (±6.3) and the most significant change in BMI occurred during the first six months of the trial (+1.1 (±2.2), P<0.0001). In fully adjusted models, there was no association between glucocorticoid exposure and change in BMI over the course of the trial (P>0.3 for all analyses). Reduced disease activity (e.g., lower BVAS/WG, ESR, CRP) was independently associated with increased BMI (P<0.0001 for all analyses), as was randomization to rituximab (P<0.02 for all analyses). There was a significant association between disease status at enrollment (new diagnosis) and increasing BMI (P≤0.04 for all analyses), but this association was lost in analyses adjusted for disease activity. Conclusions: Following the initiation of AAV treatment, changes in BMI are related more closely to improvements in disease activity than to total glucocorticoid exposure. Additional studies are necessary to identify the respective impact of glucocorticoids and disease activity on temporal variations in BMI, including adiposity and skeletal muscle mass. The observed association between rituximab and increased BMI also deserves additional evaluation. References: Curtis JR, Westfall AO, Allison J, et al. Population-based assessment of adverse events associated with long-term glucocorticoid use. Arthritis Rheum. 2006;55(3):420–426. Wung PK, Anderson T, Fontaine KR, et al. Effects of glucocorticoids on weight change during the treatment of wegener's granulomatosis. Arthritis Rheum. 2008;59(5):746–753. Stone JH, Merkel PA, Spiera R, et al. Rituximab versus cyclophosphamide for ANCA-associated vasculitis. N Engl J Med. 2010;363(3):221–232. Disclosure of Interest: None declared